SUATU KAJIAN PERBANDINGAN PENGATURAN TINDAK PIDANA PENGHINAAN TUHAN (BLASPHEMY) DI INDONESIA DAN DI BERBAGAI NEGARA ASING - Loso . (LPPM Universitas Pekalongan, 2013)
Defamation offense against God (blasphemy) of the Criminal Code has not been set explicitly, however, for the implementation of the actions that occur can be constructed in Article 156 and Article 156a of the Criminal Code. But the concept of the 2012 Criminal Code offense of contempt of God (Blasphemy) has set out clear. In some foreign countries there are clearly formulate Blasphemy in its penal code (as in the Netherlands, Finland), but also there are not formulating defamation offense against God (blasphemy) explicitly, as in Belgium, Brunei Darussalam, however blasphemous offense can still criminalized through article humiliation / desecration of religious life. Keywords: crime, blasphemy.